Art and technology: a transdisciplinary exchange, an interview with Robert Henke (Palíndromo, 2021)
The following text approaches the relation between contemporary art and other disciplines. Itis part of a series of interviews that composed a Master’s thesis research conducted by SuzzanaMagalhães de Oliveira and supervised by the professor and researcher Céline Berthoumieux forthe University of Lumière – Lyon II, in France, between 2017 and 2018. The dialogue here below,with the visual artist and musician Robert Henke, brings a reflection about how the exchangebetween the art and other knowledge domains, as the collaboration with other creators andresearchers, may be perceived in the thinking and artist’s work. The subjects mentioned in thisarticle allow us to understand better the transdisciplinarity in arts, its difficulties and the lessonsit may bring.
Keywords: Transdisciplinarity.; Contemporary art.; Electronic music.; Technology.; Artist.